Intergenerational Transmission of Educational Attainment: How Important Are Children's Personality Characteristics? - Anne Christine Holtmann; Laura Menze; Heike Solga (American Behavioral Scientist, 2021)
This study examines the role of a wide range of personality characteristics—such as the Big Five personality traits, self-esteem, goal pursuit/adjustment, social behavior, and educational aspirations—for the intergenerational transmission of educational attainment in Germany, and compares their relative importance with that of cognitive skills. We use information on more than 8,000 students from the German National Educational Panel Study. We find that personality characteristics do not mediate the association between parents' and children's attainment of the university entrance qualification (the Abitur) by age 19/20. Only educational aspirations are a strong mediator for intergenerational educational transmission. A few personality characteristics moderate intergenerational educational transmission, and they do so in favor of children with high-educated parents either as Matthew effects or compensatory advantages. In contrast to personality characteristics, cognitive skills act as strong mediators, while moderation is rather weak when accounting for personality characteristics—but again, they work in favor of privileged children. Our German study reveals similarities but also differences compared with the mostly U.S.- and U.K.-based research and inspires to rethink the importance of personality characteristics and cognitive skills for intergenerational education attainment.
doi:10.25384/SAGE.14161770.v1
Keywords: 300; noncognitive skills; personality; aspirations; social skills; competences; cognitive skills; intergenerational transmission of education; mediation; moderation